Perceptions of Older Immigrants About Health Care in the Host Countries: A Narrative Review - Ilgaz, Aysegul (Socialinė teorija, empirija, politika ir praktika, 2023)
Older immigrants may have different needs regarding health and care services compared to other age groups. There are suggestions for adapting health services to the elderly and even immigrant elderly in order to provide equal service to everyone. There are studies indicating that with advancing age chronic diseases increase and functional capacity decreases, resulting in poorer physical and psychosocial health in immigrant elderly than in the general elderly population. It is stated that immigrants’ use of health services is lower than that of general population. Cultural and social factors influence health behaviors, opportunities, wishes and barriers for patients to access and use health and care services. Studies stated that elderly immigrants not knowing how to apply for health services, having language problems and being ineffective in communication with healthcare professionals, and experiencing lack of/insufficient social, community and family support, are lead to isolation and inadequate use of health services. In the narrative review, it is aimed to explore the existing research which was conducted on the experiences and perspectives of older immigrants, formal and informal caregivers and healthcare workers regarding health and care services and as well as interventions for better adaptation of health and care services among older immigrants.
Keywords: older people; migration; health care sector; perception; experience